Synergy between UMP and MRSM have positive impact on intellectual and potential development of students - Mohammad Hakimi, Kamarudin (2019)
Understanding the need to nurture students’ potential in view of the current reality and future challenges, Universiti Malaysia Pahang (UMP) opens its doors to having cooperation to develop students’ capabilities such as the one formed with MARA Junior Science College (MRSM) that also aimed at boosting their academic growth.